Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài
Anh Thu

Chứng minh các đẳng thức :

1) (a + b)^2= a^2 + 2ab + b^2

2) ( a-b)^3=a^3-3a^2b+3ab^2-b^3

HT.Phong (9A5)
27 tháng 7 2023 lúc 8:35

1) \(\left(a+b\right)^2\)

\(=\left(a+b\right)\left(a+b\right)\)

\(=a^2+ab+ab+b^2\)

\(=a^2+2ab+b^2\left(dpcm\right)\)

2) \(\left(a-b\right)^3\)

\(=\left(a-b\right)\left(a-b\right)\left(a-b\right)\)

\(=\left(a^2-ab-ab+b^2\right)\left(a-b\right)\)

\(=\left(a^2-2ab+b^2\right)\left(a-b\right)\)

\(=a^3-a^2b-2a^2+2ab^2+ab^2-b^3\)

\(=a^3-3a^2b+3ab^2-b^3\left(dpcm\right)\)

Pons
27 tháng 7 2023 lúc 9:05

`a)` 

`(a+b)^2`

`=(a+b)(a+b)`

`=a^2+ab+ab+b^2`

`=a^2+2ab+b^2`

`->` ĐPCM

`b)` `(a-b)^3`

`=(a-b)(a-b)(a-b)`

`=(a^2-2ab+b^2)(a-b)`

`=a^3-3a^2b+3ab^2-b^3`

`->` ĐPCM


Các câu hỏi tương tự
Nguyen Minh Anh
Xem chi tiết
Nguyễn Lan Hương
Xem chi tiết
The Joker AD
Xem chi tiết
Huỳnh thái sơn
Xem chi tiết
Hanny. Ngân
Xem chi tiết
Pham Nguyen thu anh
Xem chi tiết
Phạm Thùy Linh
Xem chi tiết
Nguyễn Quang Linh
Xem chi tiết
Anh Hà Đức
Xem chi tiết